Implementasi Pembelajaran Berenang dalam Mengembangkan Keterampilan Motorik Kasar Anak Usia Dini di TK Dharma Wanita Keboansikep - Amalia, Ersa; Sari, Inez Illona; Purwaningsih, Tjatur Endah; Abdillah, Husni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
One way to develop the physical motor aspect of early childhood is by applying swimming lessons. This study aims to determine the influence of the application of swimming learning in developing children's physical motor aspects. This research method uses a qualitative method. The data collection technique was carried out by conducting observations at the Keboansikep DWP Kindergarten which consisted of 2 levels of classes A and B, and conducted interviews with educators, observations and documentation at the Dharma Wanita Persatuan Keboansikep Kindergarten. The techniques to analyze the data in this study are data reduction, presenting data, and drawing conclusions. The results of the data analysis show that Dharma Wanita Persatuan Keboansikep Kindergarten prioritizes 6 aspects of child development, of course in physical motor development. Physical motor development is the growth and development of muscles and nerves in children. This can affect early childhood skills in moving. One way to improve physical motor development is by doing swimming activities. Swimming is an activity that trains the whole body, especially children's motor skills, from head to toe